2021
DOI: 10.1007/s10811-021-02565-2
|View full text |Cite
|
Sign up to set email alerts
|

Annual production of microalgae in wastewater using pilot-scale thin-layer cascade photobioreactors

Abstract: Microalgae based wastewater treatment has been suggested as an alternative to polluting and energy-consuming conventional processes. The main advantage of this strategy is the dual role of microalgae: they recover nutrients from waste and simultaneously produce biomass with varied industrial applications. In the current study, biomass of Scenedesmus sp. was produced using primary wastewater in two pilot-scale thin-layer cascade photobioreactors (63 and 126 m 2 ). The wastewater used for microalgal growth was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…It is likely that the lower biomass productivity of the 1500 L raceway reactor used in that study (4.2 g•m -2 •day -1 ) was the reason for the lower nitrogen removal. Indeed, thin-layer cascade reactors that are highly productive allow higher areal nitrogen removal rates but allow to process less wastewater per surface area [20]. Higher removal efficiencies (85-14 98%) were observed when processing domestic wastewater using the microalga Chlorella variabilis TH03 and 3.7 m 2 raceway reactors [40].…”
Section: Nutrient Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that the lower biomass productivity of the 1500 L raceway reactor used in that study (4.2 g•m -2 •day -1 ) was the reason for the lower nitrogen removal. Indeed, thin-layer cascade reactors that are highly productive allow higher areal nitrogen removal rates but allow to process less wastewater per surface area [20]. Higher removal efficiencies (85-14 98%) were observed when processing domestic wastewater using the microalga Chlorella variabilis TH03 and 3.7 m 2 raceway reactors [40].…”
Section: Nutrient Removalmentioning
confidence: 99%
“…A limited number of studies demonstrated the robustness of Scenedesmus strains outdoors in pilot-scale reactors. This strains was recently produced using wastewater at pilot-scale using thin-layer cascade bioreactors [4,20]. Thin-layer cascade bioreactors are highly productive in terms of biomass production [21].…”
Section: Introductionmentioning
confidence: 99%
“…This microalga also showed potential for use as a feed ingredient promoting the gut functionality of fish [8] and as a biostimulant in agriculture [9]. In addition, S. almeriensis is a robust strain that can be produced using wastewater and different reactor designs [14,15] which has been suggested as key to reduce production costs [16].…”
Section: Introductionmentioning
confidence: 99%
“… Medium D, medium formulated using commercial-grade chemicals (commercial fertilisers): 1.00 g•L -1 NaNO3, 0.25 g•L -1 MgSO4, 0.30 g•L -1 KH2PO4, 30.0 g•L -1 NaCl, and 0.02 g•L -1 Karentol ® . This medium was used to produce microalgae using large photobioreactors in previous reports [10,11].…”
Section: Indoor Laboratory-scale Trialsmentioning
confidence: 99%
“…When produced outdoors using open raceway bioreactors, biomass productivity is highly influenced by environmental conditions, namely solar radiation and temperature [11]. Figure 3 [24] and Dolichospermum sp.…”
Section: Process Up-scaling: Outdoor Pilot-scale Trialsmentioning
confidence: 99%